Formulation and Sensory Evaluation of Cookies Based on Chicken Feet Bone Flour and Tofu Pulp Flour - Mustika, Ajeng (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
The use of local food ingredients and food by-products can significantly enhance food product diversification. This study explores the development of cookie formulations that incorporate chicken feet bone flour and tofu pulp flour as alternative ingredients. The objective is to assess the sensory acceptance of the resulting cookies. An experimental design was implemented with six cookie formulations: one control and five treatment formulations that varied by the amounts of chicken feet bone flour and tofu pulp flour used. Hedonic testing was conducted with 50 adult panelists to assess various sensory characteristics of the cookies, including colour, aroma, taste, texture, aftertaste, and overall liking. The data from the hedonic tests were statistically analyzed to identify differences in acceptance levels between the formulations. The results indicated significant differences in panelists' acceptance levels for color, aroma, taste, aftertaste, and overall preferences (p < 0.05). However, no significant differences were noted among the formulations regarding texture (p > 0.05). The cookies from the treatment formulation with code 849 emerged as the most preferred option among the panelists, containing 12 grams of chicken feet bone flour and 28 grams of tofu pulp flour. This study demonstrates that cookies made with chicken feet bone flour and tofu pulp flour in certain proportions can possess sensory characteristics that are well-received by panelists. The selected formulation shows promise for further development as a food product based on local ingredients.